Measurement of resistance exercise force expression - Chiu, L. Z. F.; Schilling, B. K.; Fry, A. C.; Weiss, L. W. (Journal of Applied Biomechanics, 2004)
Displacement-based measurement systems are becoming increasingly popular for assessment of force expression variables during resistance exercise. Typically a linear position transducer (LPT) is attached to the barbell to measure displacement and a double differentiation technique is used to determine acceleration. Force is calculated as the product of mass and acceleration. Despite the apparent utility of these devices, validity data are scarce. To determine whether LPT can accurately estimate vertical ground reaction forces, two men and four women with moderate to extensive resistance training experience performed concentric-only (CJS) and rebound (RJS) jump squats, two sessions of each type in random order. CJS or RJS were performed with 30%, 50%, and 70% one-repetition maximum parallel back squat 5 minutes following a warm-up and again after a 10-min rest. Displacement was measured via LPT and acceleration was calculated using the finite-difference technique. Force was estimated from the weight of the lifter-barbell system and propulsion force from the lifter-barbell system. Vertical ground reaction force was directly measured with a single-component force platform. Two-way random average-measure intraclass correlations (ICC) were used to assess the reliability of obtained measures and compare the measurements obtained via each method. High reliability (ICC > 0.70) was found for all CJS variables across the load-spectrum. RJS variables also had high ICC except for time parameters for early force production. All variables were significantly (p < 0.01) related between LPT and force platform methods with no indication of systematic bias. The LPT appears to be a valid method of assessing force under these experimental conditions.